Discovery and chemical composition of the eastmost deep-sea anoxic brine pools in the Eastern Mediterranean Sea - Herut, Barak; Rubin-Blum, Maxim; Sisma-Ventura, Guy; Jacobson, Yitzhak; Bialik, Or M.; Ozer, Tal; Lawal, Muhedeen Ajibola; Giladi, Asaf; Kanari, Mor; Antler, Gilad; Makovsky, Yizhaq (Frontiers in Marine Science, 2022)
Deep-sea anoxic brine pools are unique and extreme, yet habitable environments. However, their extent and processes of formation are not fully understood. Using geophysical analysis and seafloor surveying, we discovered the eastmost brine pools known in the ultraoligotrophic Eastern Mediterranean Sea, at the Palmahim Disturbance offshore Israel (~1150 m water depth). These brine pools are located directly above a ~1km wide piece of the Messinian evaporites section, which was up thrusted to ~350 m below the seafloor. We sampled brines and short cores to characterize the chemical composition of several small (up to 5m diameter) anoxic, methanic and warm (21.6°C) brine pools and adjacent seafloor sediments porewater. The maximal salinities measured at the pools and adjacent porewater were 63.9 and 72 PSU, respectively. The brines are characterized by enriched Na and Cl concentrations by a factor of ~1.8 and depleted Mg, SO4, K and Ca contents by factors of circa 6, 3, 2 and ~1.3, respectively, compared to the ambient seawater. Relations of the major element concentrations reveal a mixing curve between seawater and enriched Na/Cl and depleted Mg/Cl, K/Cl and SO4/Cl end-members, and do not coincide with relics of fossil residual evaporated seawater. We propose their composition reflects: 1) dissolution of Messinian halite (NaCl) by seawater, supported by their low Br/Cl ratios; 2) additional small rise in Na/Cl ratios due to the impact of clay mineral dehydration or/and dissolution of trace (~1% of the Na) amounts of detrital trona (Na3H(CO3)2•2H20), coinciding with the enriched alkalinity concentrations; 3) diagenesis processes depleting Mg, K and SO4, mainly by the formation of authigenic K-rich Mg-smectite, clay mineral dehydration, dolomitization/Mg-calcite precipitation and redox processes. The δ18O and δD values of the Palmahim brine may reflect the impact of clay mineral dehydration. Comparison to all other East Mediterranean brine lakes shows that the Palmahim brine pool system represents similar provenance of brines as observed for the Eastern Mediterranean Napoli, Nadir and Tyro lakes, while potentially recording additional processes attributed to its proximity to the coastal area.